InGaAsP-on-Insulator Platform for Nonlinear Photonic Applications: Design, Fabrication, and Challenges - Mahjoub, Rania (Université d'Ottawa / University of Ottawa, 2026)
Integrated photonics has emerged as a promising technology for realizing compact, high speed, and energy-efficient optical systems for applications including optical communications, nonlinear signal processing, and photonic computing. Among the available integrated photonic material platforms, III–V semiconductors are particularly attractive because of their direct bandgap properties, strong optical nonlinearities, and capability for integrating active and passive photonic devices on a single chip. In particular, indium gallium arsenide phosphide (InGaAsP) offers tunable bandgap engineering and compatibility with operation near telecommunication wavelengths, making it a promising candidate for nonlinear integrated photonics. This thesis investigates the development of an InGaAsP-on-insulator (InGaAsP-OI) platform through heterogeneous integration using benzocyclobutene (BCB) adhesive wafer bonding. The work addresses both fabrication challenges and nonlinear waveguide design for two distinct nonlinear processes at telecommunications-relevant wavelengths. The fabrication process includes SiO₂ deposition, BCB bonding, substrate transfer, selective wet etching, and structural characterization of the bonded platform. Particular attention is given to fabrication-induced limitations affecting the reliability and optical performance of the InGaAsP-OI platform. Experimental characterization using scanning electron microscopy (SEM), atomic force microscopy (AFM), and energy-dispersive X-ray spectroscopy (EDX) is used to investigate surface roughness, bonding quality, interfacial defects, and delamination mechanisms associated with the BCB/SiO₂ interface. In addition, nonlinear InGaAsP-OI waveguides are designed and analyzed numerically for two complementary processes. First, dispersion-engineered waveguides for four-wave mixing (FWM) are optimized using Lumerical MODE simulations, achieving a zero-dispersion wavelength of 1553 nm and a nonlinear coefficient of γ ≈ 36.9 W⁻¹m⁻¹ for the optimized geometry (w = 830 nm, h = 800 nm). Second, modal phase-matching-based second-harmonic generation (SHG) is investigated at a fundamental wavelength of 2.6 µm, exploiting the non-centrosymmetric zinc-blende crystal structure of InGaAsP to achieve χ⁽²⁾-based frequency conversion without additional quasi-phase-matching structures. A phase-matched waveguide geometry is identified through analytical mode simulations, and the modal overlap and SHG conversion efficiency are quantified. The results demonstrate the potential of InGaAsP-OI structures for compact, chip-scale nonlinear photonic circuits operating at telecommunications wavelengths, while highlighting the critical role of fabrication optimization and bonding reliability in the development of practical III–V-on-insulator nonlinear photonic platforms.
Keywords: Integrated photonics; Adhesive wafer bonding; Four wave mixing (FWM); Secomd harmonic generation (SHG)